(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable of all creatures, and upon his family myamine. To follow the reform and educational approach of the Prophet, may God bless him and his family, in the nation, the researcher is required to To spend a large part of his life trying to be aware of those bright aspects in the life of the nation.